A phase II, single-center, randomized, double-blind, parallel control clinical study evaluating the immunogenicity and safety of a two-dose schedule of serogroups ACYW meningococcal polysaccharide conjugate vaccine. Issue 47 (8th November 2022) - Mo, Yi; Li, Yanan; Liu, Gang; Chen, Junji; Wei, Dingkai; Wu, Jigang; Meng, Qiuyan; Li, Zhi; Mo, Zhaojun
Abstract: Background: This was a single-center, randomized, double-blind, parallel control study evaluating the immunogenicity and safety of a two-dose schedule of serogroups ACYW meningococcal polysaccharide conjugate vaccine with tetanus toxoid (TT) conjugate protein, in infants and toddlers of 3–35 months old. Method: 720 participants were stratified according to the age of 3–5 months old, 6–11 months old, and 12–35 months old and randomly assigned with an equal ratio to two different dose groups, i.e., 40- and 20-μg doses. Blood samples were taken from all participants before the first vaccination and 30 days after the full-course vaccination to detect the serogroups ACYW meningococcal antibodies. All adverse events occurred within 30 days after vaccination of each dose, and serious adverse events occurred within six months after full-course vaccination were collected for safety evaluation. This study was registered at the China drug trial registration with the identifier CTR 20182031. Results: After 30 days of full-course vaccination, 92.78 % (95 % CI: 85.70 %-100.00 %) showed the immune response against all serogroups in both high-dose and low-dose groups by rabbit serum bactericidal antibody assay (rSBA) and the geometric mean titer (GMT) of all serogroups showed a high level (74.6–505.8, 95 % CI: 56.4–615.7). However, no significant difference between different dose groups was observed (P > 0.05). The common local and systemic adverse events in both groups were redness (3 %-7%), and fever (26 %-65 %), respectively. In addition, the grade 3 adverse event related to the vaccine was fever (1.67 %-12.50 %). No serious adverse event was reported to be associate with the vaccination. Conclusion: The serogroups ACYW meningococcal polysaccharide conjugate vaccine was safe and effective in the population aged 3–35 months. The vaccine efficacy and safety of the 20-μg dose group were not less than that of the 40-μg dose group.